Exclusion through Language: A Reflection on Classroom Discourse in Tanzanian Secondary Schools - Vuzo, Mwajuma (Papers in Education and Development, 2018)
This paper discusses classroom discourse in Tanzanian secondary schools in the light of English as the medium of instruction. There are several factors influencing classroom interaction inTanzania. This paper will be confined to the medium of instruction as the prime factor. Other factors will, however, be highlighted. The use of English as the medium of instruction inTanzaniasecondary school is a barrier to learning and in fostering classroom interaction. The language of instruction barrier contributes to a majority of students being excluded in classroom dialogue. Drawing upon the ideas of various theorists on classroom discourse and learning and from findings of recent studies, it is recommended that the use of a familiar language such as Kiswahili will promote effective teaching and learning and maximize classroom interaction. In addition, the need to improve learning conditions is highlighted so as to achieve the goal of effective classroom interaction. Suggestions are also given for strategies that can be used to promote interactive learning.